TACIT AND THE SIGNIFICANCE OF YOUR MEMORY - Viveros González, Ana Francisca (Revista de Historia Social y de las Mentalidades, 2011)
Cornelius Tacitus was a prominent roman historian from the I century AD, has been extensively studied from various perspectives, though never studied the trascendence of the memory in his work, this current analysis focuses on this. Thus it conceives history as justice, memory plays a fundamental role in his story. Therefore, clarify how Tacitus understood history and his relation to memory, the relationship between them and how memory is represented in his work, trough three categories of analysis, namely: memory as action, as memories and as trascendence. This will demonstrate the integration he made of issues that are current to our times such as the transmission of values and the critic judgement made over the history, but especially the idea that between history and memory exist a dialectic that allows the perpetuation of the memory through the history.